(3GdQSGdI GdHgGFjI aj GdMSGHs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s ((3CHh WGdH Hf MSf Hf eMeO GdMdi s)
(3ChdgG (B:s
(3GdMeO ddChd HdG YOO hGdCNQ HdGfO hHYO adeG cGf cGf Yde GdbhGfjf GdMSGHjI hGdeSGFd GdYOOjI s
(3BNQgG (B:s
(3hHYVgG GdChd ef GdCcKQ gPg BNQ GdahGFO GdgGeg ai GdbhGYO GdMSGHjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(61) s
Keywords: (3GdeLGejYs